"Roža Niča" - Snoj, Vid (Primerjalna književnost, 2018)
The Holocaust or the Shoah, the Jewish catastrophe, looms large in Paul Celan's oeuvre, starting with his early and most famous poem, "Death Fugue". Celan's poetic treatment of the Jewish catastrophe gradually came to include Jewish mysticism, addressed perhaps most deeply in his "Psalm". This poem lends voice to the victims - not those waiting for death in an extermination camp, as in "Death Fugue", but to the dead ones, the murdered ones. The speakers of "Psalm" are addressing No One, meaning God, as if they were reducing God to nothing. This calls to mind Nietzsche's declaration that "God is dead", according to which God or the supersensory world, the world of ideas as values which used to endow earthly life with sense and vigour, can offer nothing more. However, Celan's speakers are not talking about God but to God, addressing him as No One. On the other hand, they refer to themselves, unburied, gassed, cremated, and left to rise into the air like smoke, as to "Nothing-Rose" and "No-One's-Rose" - a rose which blooms without soil toward, or in spite of, Nothing. It is here that Celan introduces Jewish mysticism: in the Kabbalah, "Nothing" ('Ayin) is a name for the first sefirah, the beginning of God's revelation, the revelation of 'Ayin-Sof, the Infinite, before Creation. The so-called tsimtsum, the crossing of the Infinite into the dimension of being and its simultaneous retreat back into transcendence, the "inside-out-treat", which is continuously going on as the beat of God's life, was interpreted by Gershom Scholem, the major historian of Jewish mysticism and an author who was familiar to Celan, as God's having fully retreated into the nothing of revelation. The same line of thought, which might be dubbed "religious nihilism" as opposed to Nietzschean atheist nihilism, is presumably pursued by Celan.
Keywords: Celan, Paul, 1920-1970; German poetry; Holocaust; nemška poezija; holokavst; Bible; The Holocaust; Biblija; Jewish mysticism; judovska mistika; Kabbalah; revelation; kabala; razodetje; religious nihilism; religiozni nihilizem